Variation of Phenolic Content in Globe Artichoke in Relation to Biological, Technical and Environmental Factors - Sara Lombardo; Gaetano Pandino; Rosario Mauro; Giovanni Mauromicale (Italian Journal of Agronomy)
In Italy, globe artichoke production is prevailingly concentrated in the South and islands, where it provides an important contribution to the agricultural economy. In recent years, there has been a renewed interest in this crop as a promising source of polyphenols, a heterogeneous class of secondary metabolites characterized by various healthy properties well-documented in literature. The phenolic fraction, present in the different artichoke plant parts, varies widely in relation to biotic and abiotic factors. Therefore, the present study aimed at evaluating the variation of phenolic content in globe artichoke in relation to biological, technical and environmental factors. Two field-experiments were carried out in Sicily (South Italy) in two representative cultivation areas, in order to examine the effects of genotype, head fraction, season conditions, planting density and arrangement on the globe artichoke phenolic concentration. Both the total polyphenols and the individual phenolic compounds detected were notably genotype- dependent. Particularly, the high level of caffeoylquinic acids (chlorogenic acid, among others) and apigenin 7- O-glucuronide, reported respectively by “Violetto di Sicilia” and “Romanesco clone C3”, could be used to encourage globe artichoke fresh consumption. Total polyphenols content also resulted more abundant in specific accumulation sites within the inflorescence, such as the floral stem and receptacle, and for most of genotypes it decreased during the second year in response to the different meteorological conditions. Additionally, total polyphenols content significantly and linearly increased as plant density increased from 1.0 to 1.8 plant m-2 and it significantly increased by 13% passing from single to twin rows plant arrangement.